2017
DOI: 10.1016/j.renene.2016.12.068
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive pitch control of wind turbine for load mitigation under structural uncertainties

Abstract: In this research, a new adaptive control strategy is formulated for the pitch control of wind turbine that may suffer from reduced life owing to extreme loads and fatigue when operated under high wind speed and internal structural uncertainties. Specifically, we aim at making a trade-off between the maximum energy captured and the load induced. The adaptive controller is designed to both regulate generator speed and mitigate component loads under turbulent wind field when blade stiffness uncertainties exist. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…As presented by Li [29] and Yuan [30], one way to analyze the ASPR property of a nonlinear system is to linearize it at different operating points and verify whether the system is non-minimum-phase and whether the product of matrices CB is positive. However, this results in an infinite number of operating points to be analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As presented by Li [29] and Yuan [30], one way to analyze the ASPR property of a nonlinear system is to linearize it at different operating points and verify whether the system is non-minimum-phase and whether the product of matrices CB is positive. However, this results in an infinite number of operating points to be analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Because the ASPR properties presented are applicable for LTI systems only, one way to ensure the ASPR property for a nonlinear plant is to linearize the plant at different operating points and evaluate the ASPR requirements at these points [29,30].…”
Section: Theorem 2 Ifmentioning
confidence: 99%
“…For example, in Lasheen and Elshafei, a fuzzy Takagi‐Sugeno model is constructed and used for prediction in a model predictive controller. In many applications, a linear approximation of the wind turbine model around its nominal operating point is used (Novak et al and Yuan and Tang). However, since the average wind speed is varying, the PWL models obtained around different wind speeds can provide much more accurate representation of the real wind turbine dynamic.…”
Section: Wind Turbine Modelingmentioning
confidence: 99%
“…Adaptive control was developed by [14] with disturbance rejection and load mitigation capabilities for onshore wind turbines. It was shown that the adaptive controller was better in load mitigation than the baseline controller employed by FAST [7] but, at a cost of degradation in power regulation.…”
Section: Introductionmentioning
confidence: 99%